2011
DOI: 10.3892/ijo.2011.1222
|View full text |Cite
|
Sign up to set email alerts
|

Importance of retinoic acid-inducible gene I and of receptor for type I interferon for cellular resistance to infection by Newcastle disease virus

Abstract: Abstract. Newcastle disease virus (NDV) is an avian paramyxovirus with oncolytic properties which shows promising effects in the treatment of cancer. Anti-cancer effects are due to the virus ability: i) to replicate in and kill tumor cells, leading finally to their selective elimination; and ii) to induce the stimulation of antitumor activities in immune cells. NDV does not harm normal cells and has a high safety profile. In this study, we first report a direct correlation between the degree of cell resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…In normal cells of non-permissive hosts (rodents, humans), signaling via RIG-I (intracellular recognition of viral RNA) and amplification via an IFN induced feedback loop by membrane-expressed type I IFN receptor (IFNRA) [61] leads to an effective interferon response, induction of anti-viral gene expression and prevention of NDV replication. NDV and NDV-induced IFNα is involved in polarization of DCs towards DC1, a genetic programming process that only takes 18 h and involves 24 transcription factors leading to upregulation of 779 genes [62].…”
Section: Special Characteristics Of Ndv and Other Paramyxovirusesmentioning
confidence: 99%
“…In normal cells of non-permissive hosts (rodents, humans), signaling via RIG-I (intracellular recognition of viral RNA) and amplification via an IFN induced feedback loop by membrane-expressed type I IFN receptor (IFNRA) [61] leads to an effective interferon response, induction of anti-viral gene expression and prevention of NDV replication. NDV and NDV-induced IFNα is involved in polarization of DCs towards DC1, a genetic programming process that only takes 18 h and involves 24 transcription factors leading to upregulation of 779 genes [62].…”
Section: Special Characteristics Of Ndv and Other Paramyxovirusesmentioning
confidence: 99%
“…NDV induces in human PBMC, DCs and monocytes a strong type I IFN response [4,6,15,40]. This occurs within 18–24 h and consists of an early phase and a late phase.…”
Section: Immunobiologymentioning
confidence: 99%
“…The studies revealed an important role in the IFN response of RIG-I, IRF3, IFN-β and IRF7 [6,27]. In addition, studies with cells from Knock-out mice devoid of the gene for IFNRA showed the importance of this receptor: In its absence, normal cells were incapable of preventing NDV replication [49,50].…”
Section: Immunobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Complete cellular resistance to NDV infection has been demonstrated in mammalian cells lacking specific sialylated moieties (mainly gangliosides, and N-syalilated glycoproteins) on the cell surface (absence of receptors) [20], while increased tolerance to NDV-induced cell death in cell culture has been associated with the presence of specific intracellular pathogen sensors – such as Retinoic Acid-Inducible Gene I (RIG-I) [21, 22]; increased type-I interferon response [23, 24]; and activity of the Mx protein family [2527]. Also viral interference, although not a cellular resistance per se , inhibits NDV superinfection [28–30].…”
Section: Introductionmentioning
confidence: 99%